Quantitative crack evaluation in slender reinforced concrete walls with rectangular section - Priyana Rajbhandari; Chanipa Netrattana; Taku Obara; Kono Susumu (Resilient Cities and Structures, 2024)
Past earthquakes have shown that cracking affects post-earthquake functionality and accounted for huge repair costs for reinforced concrete (RC) wall buildings, even though the code-compliant seismic design prevents collapse. Engineers should know the maximum residual flexural crack width and volume of repair material needed for the flexural cracks to determine the damage degree and the repair cost. This paper presents the experimental campaign on four RC slender walls that investigated the effect of confining reinforcement and thickness of the wall on flexural crack parameters under quasi-static reversed cyclic loading. The width of all flexural cracks was measured when reaching each cycle peak drift and when unloading to zero lateral loads. Crack widths at peak and residual states increased with increasing peak drift. Based on the experimental observations, it was found that the maximum residual crack width is obtained as a simple function of the extreme tension fiber elongation of the wall tensile fiber within ±30% error. In addition, this paper outlines methods to calculate the volume of repair material for flexural cracks from the extreme tension fiber elongation of the wall. With the fundamental rules found from the experiment in this paper, it will become possible to obtain the maximum crack width and the volume of repair material from simple numerical analysis tools such as a multi-spring line element model.